IMPLEMENTATION OF ROOT CAUSE ANALYSIS METHOD TO INVESTIGATE FAILURE OF FRONT WALL TUBE BOILER - Febriyanti, Eka; Suhadi, Amin; Sari, Laili Novita (Majalah Ilmiah Pengkajian Industri, 2020)
Root cause analysis is a method that observes all of the possible causes that make the system or components fail. This research is implemented such a method to investigate the failed front wall tube on the boiler. The purpose of this research is to find out the main cause of failure on the front wall tube to avoid a similar problem in the future.  Considering all aspects that have the potential to be the main cause of failure, therefore, many tests and examinations are done, including visual tests, fractography, metallography, chemical analysis, hardness test, SEM, and EDS analysis.  Examination result on the fracture surface shows two bulges on a tube and some longitudinal cracks spread on bulges outside the surface area. At the same time, the thick scale is also found on the inside surface of these bulges. Moreover, microstructure and hardness changes are also found in this area.  From the analysis of all test result that obtained it is concluded that the main cause of failure is the presence of scales which reduce heat transfer so that local overheating occurred.  Consequently, its tensile strength in this area is decreased, and finally, the tube could not support operational pressure and deformed to make a bulge.      Keywords: Root cause; Failure; Front wall; Tube; Boiler